Investigating L2 Phonological Acquisition from Different Perspectives: An Introduction to the Special Issue - Alex Ho-Cheong Leung; Natalia Pavlovskaya; Martha Young-Scholten (Languages)
Building on the existing literature including recent Special Issues, edited volumes, and feature articles on the study of second language (L2) phonetics and phonology (e [...]